Eksistensi Bumdes Dalam Upaya Meningkatkan Perekonomian Masyarakat Di Kecamatan Jatinangor Kabupaten Sumedang - Agni Grandita Permatasari (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
BUMDes is very important for village independence because one of its aspects is the economic ones. In the midst of the strong spirit of developing villages in West Java, it turns out that many BUMDes are freezed, one of which is in Jatinangor District. This paper aims to find out the condition of BUMDes in Jatinangor District and efforts to make BUMDes independent. The results of this study indicate that although most villages already have BUMDes, they are only engaged in the waste disposal sector so that they do not contribute to PADes. Then, there are efforts that can be made to make BUMDes independent, including strengthening the improvement of the quality of human resources, and network development.